Effect of the abiotic factor on Schleichera oleosa chlorophyll level - Rahmah, Azizatur; Rahmawati, Diah Lailil (El-Hayah : Jurnal Biologi, 2021)
Chlorophyll in Schleichera oleosa is important to observe because S.oleosa is a tree plant that is often found on the road as a green plant. This role requires sufficient chlorophyll to maximize plant function for photosynthesis. Photosynthesis is supported by environmental factors. There are several environmental factors needed to maximize photosynthesis, namely altitude, humidity, ambient temperature, and light intensity. This study wanted to determine the effect of altitude, air humidity, ambient temperature, light intensity with chlorophyll content in S. oleose in several places. Altitude is measured using GPS. Measurement of air temperature and wind speed were measured using the Altimeter sights ler application version 2.0. Light intensity is measured using a lux meter. Soil moisture and soil pH were measured using a soil tester. Chlorophyll levels were measured using a spectrophotometer with a wavelength of 665 and 649, chlorophyll was calculated using the Wintermans and De Mots formula (1965). The results showed that chlorophyll content increased with increasing altitude. At the highest altitude of 833.6 m asl, the chlorophyll content is 53,770 with an ambient temperature of 270C which decreases at an altitude of 833.6 m asl.